Digital Control for a PV Powered BLDC Motor - Slamet Riyadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Stand-alone applications of Photovoltaic (PV) can be found in water pumping systems for rural area. The proper electric motor must be chosen for optimal considerations. One of the modern electric motor called brushless motor (BLDC) can be an alternative for this application although it has complexity in control. Powering such a motor by using electric energy generating by PV modules will be an interesting problem. In this paper, a PV powered BLDC motor system is proposed. The PV modules must produce maximum power at any instant time and then this power must be able to rotate the motor. By combining sequential stator energizing due to a rotor detection and a PWM concept, the speed of BLDC can be controlled. Meanwhile, to get maximum power of PV modules, detection of voltage and current of the modules are required to be calculated. Digital Signal Control (DSC) is implemented to handle this control strategy and locks the width of the PWM signal to maintain the PV modules under maximum power operation. The effectiveness of the proposed system has been verified by simulation works. Finally the experimental works were done to validate.